Preparação e caracterização de óxidos de ferro magnéticos revestidos com polidimetilsiloxano - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
The development of magnetic nanoparticles has been a studying object, due to possible applications in knowledge areas as: physics, chemistry and biology. In this study was made synthesis of magnetic iron oxide and was made its polymeric coating with polydimethylsiloxane oil (PDMS). The aim was to investigate the effect of the magnetic iron oxide particles coated with PDMS, which can be used to enquiry from the dragging effects and removal of nonpolar organic compound in aqueous systems. The magnetic iron oxide was synthesized with the coprecipitation method by alkaline hydrolysis of ions Fe2+ and Fe3+ in aqueous system. The coated particles were obtained by heating mixed magnetic iron oxide and PDMS oil from 50 to 250°C for 30 minutes. In this way was obtained magnetic dust particles with hydrophobic behavior. The samples was characterized by: Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), Chemical analysis by potenciometric titration, thermogravimetric analysis (TGA), transmission electron microscopy (TEM), vibrating sample magnetometry (VSM), contact angle measurement and spectroscopy Mössbauer. The diffractogram of X-ray presented peaks that was assigned to presence of spinel structure with medium sized crystallites of 10,95 for the polymeric coated magnetic iron oxide confirmed by TEM with superparamagnetic character confirmed by VSM. The infrared spectrum showed absortion band in 570 cm-1 characteristic of the Fe-O bonding in inverted spinel structure and the absortion band in 800 cm-1 characteristic of the Si-O-Si, indicating the presence of PDMS on the magnetic iron oxide particles. The thermogravimetric analysis determined the amount of polymeric material (9,7  4%) on the inorganic matrices and through contact angle measurement, was possible verify that the coated samples at 250°C presented a bigger nonpolar character in comparison to the coated samples at 50°C. The samples under room temperature (300K) presented the phases (magnetite, maghemite, goethite) confirmed with the Mossbauer spectroscopy. It was possible through the used methodology, obtain magnetic particles coated with PDMS, which magnetic and hydrophobic properties was appropriate for the removal of small fraction of hydrophobic liquids of the water surface, in preliminary test.
Keywords: Nanopartículas; Óxidos de ferro magnéticos; Polidimetilsiloxano; Remoção de compostos apolares; Nanoparticles; Magnetic iron oxide; Polydimethylsiloxane; Removal of nonpolar compounds; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA